Optimization of fermentation technology and its in-vitro activity of hawthorn enzyme - MIAO Yuanxin; TIAN Jianyang; BI Jinhua; PENG Xinyu; GAO Jia (Shipin yu jixie)
ObjectiveHawthorn enzyme was prepared from hawthorn by using the mixed strains of Lactobacillus plant-based and saccharomyces cerevisiae with high activity, and its fermentation process and biological activity in vitro were investigated.MethodsThe effects of solid-liquid ratio, inoculant number of mixed strains, initial sugar degree, fermentation time and fermentation temperature on the quality of hawthorn enzyme were studied with acidity, soluble solid content and superoxide dismutase SOD activity as experimental indexes. The optimal fermentation conditions of hawthorn enzyme were determined by response surface test, and the biological activity of hawthorn enzyme in vitro was analyzed.ResultsThe optimum fermentation parameters were liquid-solid ratio 1∶3 (g/mL), inoculated amount of mixed fermentation strains 5.5‰, initial sugar content 11.4%, fermentation time 102 h and fermentation temperature 32 ℃. Under the control of those conditions, the acidity, soluble solids content and SOD activity of hawthorn enzyme were （21.82±0.26） mg/mL, （10.75±0.29）%, （26.45±0.31） U/mL, respectively. In addition, hawthorn enzyme had obvious scavenging ability on DPPH·, ABTS· and ·OH, and some pancreatic lipase inhibitory activities.ConclusionThe enzyme has good inhibitory activity of pancreatic lipase and antioxidant activity.